2021
DOI: 10.3390/microorganisms9122504
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Resistance-Related Phenolics: A Study of Plant-Associated Bacteria and Hymenoscyphus fraxineus

Abstract: European ash (Fraxinus excelsior) is highly affected by the pathogenic fungus Hymenoscyphus fraxineus in all of Europe. Increases in plant’s secondary metabolite (SM) production is often linked tol enhanced resistance to stress, both biotic and abiotic. Moreover, plant-associated bacteria have been shown to enhance SM production in inoculated plants. Thus, our hypothesis is that bacteria may boost ash SM production, hence priming the tree’s metabolism and facilitating higher levels of resilience to H. fraxineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…can produce different amounts of phenols, flavonoids, and photosynthesis pigments [ 31 ]. Furthermore, we observed the same tendencies in ash, spruce, and pine trees as well as blueberries and lingonberries [ 32 , 43 , 47 , 53 , 54 ]. All these examples align perfectly with the findings of this study, whereby we observed statistically significant differences in the amounts of TPC, TFC and antioxidant scavenging capacity diverging in different half-sib families grown in the same site and belonging to the same population.…”
Section: Discussionsupporting
confidence: 67%
“…can produce different amounts of phenols, flavonoids, and photosynthesis pigments [ 31 ]. Furthermore, we observed the same tendencies in ash, spruce, and pine trees as well as blueberries and lingonberries [ 32 , 43 , 47 , 53 , 54 ]. All these examples align perfectly with the findings of this study, whereby we observed statistically significant differences in the amounts of TPC, TFC and antioxidant scavenging capacity diverging in different half-sib families grown in the same site and belonging to the same population.…”
Section: Discussionsupporting
confidence: 67%
“…in Europe and is not associated with P. abies. The detection of H. fraxineus in different samples of the study was probably due to the presence of its propagules on the surface of different tissues (needles, shoots, or roots) and in the soil as the surface of our samples was not sterilised, and the disease caused by this fungus is active in the area [107]. The soil and tree roots were commonly colonised by mycorrhizal fungi (Table 4, Figure 7), which may also have limited the occurrence and activity of pathogenic fungi [108].…”
Section: Discussionmentioning
confidence: 91%
“…It is worth noting that the five tested Pinus sylvestris half-sib families exhibited different responses to JA application. Previous related studies show that different genotypes from the same species can exhibit varied production of secondary metabolites, antioxidant activity and growth [ 15 , 16 ]. Similar variations were observed in Norway spruce as well [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-enzymatic antioxidants include ascorbate, glutathione and photosynthesis pigments, such as carotenoids [ 12 , 13 , 14 ]. Additionally, plant response indirectly could be indicated through other photosynthesis pigments (i.e., chlorophylls) [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%